The chemistry, pharmacologic, and therapeutic applications of Polyalthia longifolia - K. V., Katkar; A. C., Suthar; V. S., Chauhan (Pharmacognosy Reviews, 2010)
Medicinal plants are nature's gift to human beings to lead a disease-free, healthy life. They play a vital role in preserving our health. India is one of the most medicoculturally diverse countries in the world, where the medicinal plant sector is part of a time-honored tradition that is respected even today. Medicinal plants are believed to be much safer and proved as elixir in the treatment of various ailments. In our country, more than 2000 medicinal plants are recognized. Polyalthia longifolia cv. pendula (Annonaceae) is native to the drier regions of India and is locally known as “Ashoka” and is commonly cultivated in Pakistan and Sri Lanka. This plant is used as an antipyretic agent in indigenous systems of medicine. Pharmacologic studies on the bark and leaves of this plant show effective antimicrobial activity, cytotoxic function, antiulcer activity, hypoglycemic activity, and hypotensive effect. The present article includes the detailed exploration of pharmacologic properties of P. longifolia in an attempt to provide a direction for further research.
Keywords: Polyalthia longifolia; phytochemicals; pharmacologic action